Sound-space: a listener’s creative outcome through an acousmatic performance at the Spatial Sound Institute - Balbontín Gallo, María Sofía. (Routledge, 2024)
This research focuses on the invisible space built by sound as subject of study, developing through a practice-based methodology a creative process during a residency period in the Spatial Sound Institute (SSI), mainly to investigate the sound features of non-existing architectures. The process ended with a performance that invited listeners to experience a deeper awareness of perception for reaching spaces that exceed the limits of physical possibilities. In this sense, active listening becomes fundamental, not only for forming a personal interpretation of this expanded reality, but for creating sound-spaces from a performative experience.
Keywords: Audible architecture; Sound-space; Sinestesia; Percepción; Desempeño humano